Dynamic balancing of two-plane rotor without phase angle measurement using amplitude subtraction method. (October 2019) - Bhende, Amit R
Two-plane balancing is required for a rotor whose length is greater than its diameter. Balancing such a rotor is tricky, since the effects of unbalanced forces on both the planes need to be considered in determining the corrective action. This article presents a method of dynamic balancing of a two-plane rotor without the need to measure the phase angle. The rotor is balanced by measuring vibration amplitudes at the support bearing of the rotor shaft. A new rotor balancing method of amplitude subtraction is used to calculate the balancing weights and their positions on the rotor. The advantages of this method over the phase angle measurement method are also discussed in the article.